Comparison of two types of high-intensity interval training: heart rate based vs. speed/time based - Radgiglou, S. N.; Safarzade, A.; Shirinbayan, V. (Asian Journal of Sports Medicine, 2022)
Background: Monitoring exercise intensity accurately is a constant concern for athletes and researchers. Objectives: The objective of this study was to compare the effects of controlling high-intensity interval training (HIIT) with heart rate (HTHR) and speed/time (HTST) on some fatigue-related variables. Methods: Twenty young male athletes (age 22.75 ± 2.5 years, weight 76.6 ± 8.8 kg, height 179.7 ± 6.5 cm) were randomly allocated to one of the two arms. Then two-time acute running was performed with intensity control based on heart rates (HR) and speed/time for 40 min on the treadmill with a one-week washout. In order to measure vVO2max, a VIFT test (30 - 15 intermittent fitness test) was taken. Serum levels of glucose, lactate, glycerol, pyruvate, and creatine kinase were measured before and at the end of each exercise. The normality of data was determined by the Shapiro-Wilk test. The t-test and univariate test were used to analyze within- and inter-group changes between the two types of HIIT, respectively. Results: The speed decreases at the identical intensity HTHR over time. The average speed in HTST was significantly higher (P < 0.05), but the maximum and minimum speed in HTHR was significantly higher and lower, respectively. The average distance covered by subjects in HTST was significantly higher (P < 0.05). The post-exercise blood fatigue indexes (i.e., pH, creatine kinase, lactate, glycerol, lactate/pyruvate, and glucose) in HTHR was significantly less compared to those in HTST. Heart rate increases at the identical intensity based on vVIFT in HTST gradually. Conclusions: In general, HTHR can exert the recovery and relative intensity between subjects more accurately. In fact, training based on HR, in contrast to speed/time, decreases internal load differences and increases external load differences between individuals.